2007
DOI: 10.1016/j.jfca.2007.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The nutrient composition of South African lamb (A2 grade)

Abstract: Dorper and Merino lamb carcasses of the A age group with a fat code 2 (±7% SCF) from three main production areas in South Africa were used for this study. The right sides of the carcasses were used to determine the raw nutrient and physical (carcass) composition of each cut as well as for the whole carcass by calculation. Three cuts (shoulder, loin and leg) from the left side were cooked in order to determine the nutrient composition thereof. Nutrients showing the greatest differences between raw and cooked tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…He did, however, admit that the amount of untrimmed fat (mostly seam fat), increased with increase in fat score. Considering the ratios of intermuscular fat to SCF of retail cuts of a fat score 2 carcass (Table 7; Van Heerden et al, 2007), the total fat of shoulder, leg and loin cuts will be ~7, 12 and 29%, respectively (calculated from Table 6). If these cuts were trimmed to SCF levels equal to fat score 1, the remaining fat will be ~4, 7 and 13 %, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…He did, however, admit that the amount of untrimmed fat (mostly seam fat), increased with increase in fat score. Considering the ratios of intermuscular fat to SCF of retail cuts of a fat score 2 carcass (Table 7; Van Heerden et al, 2007), the total fat of shoulder, leg and loin cuts will be ~7, 12 and 29%, respectively (calculated from Table 6). If these cuts were trimmed to SCF levels equal to fat score 1, the remaining fat will be ~4, 7 and 13 %, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…For the purpose of benchmark values, deboning data including SCF and IMF proportions of different cuts of the lamb carcass with a fat score of 2 were obtained from the study of Van Heerden et al (2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The animal (genetics), nutrition (grain-fed or pasture-grazed), meat cut and fat trimming influence the total fat content of beef and mutton portions (Schönfeldt and Welgemoed, 1996;Droulez et al, 2006;Scollan et al, 2006;Van Heerden et al, 2007). In beef, the fat is present as membrane fat (phospholipids), intermuscular fat and as subcutaneous fat, while marbling refers to the adipose tissue between the bundles of muscle fibres (Scollan et al, 2006).…”
Section: Red Meatmentioning
confidence: 99%
“…According to the 1999 edition of the Composition of South African Foods, the fat content of lamb was listed as 21.6% (Sayed et al, 1999), but these data were derived from the United States Department of Agriculture Food Composition Database, which has since been updated. Recent studies on the most commonly consumed South African lamb and mutton cuts reported fat values of o10% on an average (Van Heerden et al, 2007).…”
Section: A Science-driven Solutionmentioning
confidence: 99%